Correction: Synchrotron macro ATR-FTIR microspectroscopy for high-resolution chemical mapping of single cells. Issue 14 (17th June 2021) - Vongsvivut, Jitraporn; Pérez-Guaita, David; Wood, Bayden R.; Heraud, Philip; Khambatta, Karina; Hartnell, David; Hackett, Mark J.; Tobin, Mark J.
Abstract : Correction for 'Synchrotron macro ATR-FTIR microspectroscopy for high-resolution chemical mapping of single cells' by Jitraporn Vongsvivut et al., Analyst, 2019, 144, 3226–3238, DOI: ; 10.1039/C8AN01543K .